Sociedad en red 8 E.G.B. Tercer Ciclo - BRUNO, Paula; COSSE, Isabella; JUNGMAN, Esteban; KWIATKOWSKI, Nicolás; LICHTENSZTEIN, Andrea; VERARDI, Julián (A-Z, 2000)
AUTORES:CALVO, Graciela; DAMIN, Roberto; SCHMITT, Nancy; CASTELLANI, Ana; AGUERRE, Marina; CONSTANTIN, María Teresa Coord.; PENHOS, Marta; macri, mARíA DEL rOSARIO; TAUBER, Ricardo